Transition metal oxide / conductive polymer gel and preparation method thereof, negative active material, negative pole piece and lithium ion battery
By mixing transition metal oxide with conductive polymer monomer and phytic acid, the gel material prepared is solved in the prior art, which has poor cycle stability, low electron conduction capacity and insufficient energy storage capacity during high magnification and long-term cycles, and the specific capacity, cycle stability and rate performance are improved.
Patent Information
- Application Number
- CN202411944918.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
AI Technical Summary
The existing transition metal oxide anode materials have problems such as poor cycle stability, low electron conduction capacity and insufficient energy storage capacity during high magnification and long-term circulation.
The transition metal oxide/conductive polymer gel is prepared by mixing the transition metal oxide with the conductive polymer monomer and phytic acid. The doping and crosslinking of phytic acid are used to form a three-dimensional continuous electron transport network to improve the conductivity and viscosity of the material.
The specific capacity, cycle stability and rate performance of transition metal oxides as negative electrode materials are improved, the electrode preparation process is simplified, the production cost is reduced, and the potential for large-scale production is provided.
Smart Images

Figure CN119650662A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a transition metal oxide / polymer gel and a preparation method thereof, a negative electrode active material, a negative electrode sheet, and a lithium ion battery. Background Art
[0002] Lithium-ion batteries (LIBs) have been widely used as the main energy source for portable electronic devices, and their application scope is expanding to larger-scale fields, especially electric vehicles and grid energy storage. As the demand for application fields continues to increase, the development of high-performance energy storage electrode materials has attracted great attention.
[0003] As a key component of lithium-ion batteries, negative electrode materials can release lithium ions and store lithium ions during the recharging process. Graphite is a commonly used negative electrode material, but its theoretical maximum lithium embedding capacity is limited. When lithium ions are embedded, part of the solvent in the electrolyte will be embedded along with it, resulting in structural changes, which cannot meet the requirements of high power and large capacity.
[0004] Transition metal oxides have a high theoretical specific capacity and are considered to be a promising negative electrode material. α-Fe2O3 is a non-toxic, low-cost material with a theoretical capacity of 1007 mAh g -1 ) is much higher than commercial graphite (372mAh g -1 ), and is considered to be a very promising negative electrode material. However, due to the large volume change during battery cycling and the limitations of its electron / ion dynamics, Fe2O3 still faces many challenges during high-rate and long-term charge and discharge cycles, including: (i) During the electrochemical reaction, Fe2O3 expands / contracts to a large extent as ions are inserted / extracted, and the resulting stress can cause structural damage or even collapse, resulting in poor cycle stability; (ii) Poor conductivity leads to slow charge transfer, resulting in poor rate performance; (iii) Slow ion transport causes many active centers to be unable to contact electrolyte ions, affecting the full utilization of its energy storage capacity.
[0005] There are methods to solve the above problems by constructing nanostructured metal oxides, such as nanowires, nanorods, nanosheets, etc., or constructing composite materials of nanostructured metal oxides and carbon materials / conductive polymers. Among them, the composite materials constructed by nanostructured metal oxides and conductive polymers have higher specific capacity than metal oxide electrode materials constructed by other methods, and therefore have attracted much attention. Most metal oxide / conductive polymer composite materials exist in the form of a layer of conductive polymer (shell) formed on the surface of the metal oxide (core). The conductive polymer layer interacts with the metal oxide, electronic coupling occurs, and the electronic conductivity of the metal oxide is significantly improved.
[0006] Although metal oxide / conductive polymer composites can improve energy storage capacity and rate performance, their energy storage capacity is still far from their theoretical value. The reasons may be: (i) The conductive polymer layer formed on the surface of the metal oxide will hinder the contact between the electrolyte ions and the metal oxide to a certain extent, limiting its full energy storage capacity, resulting in a relatively low specific capacity; (ii) Most metal oxide / conductive polymer composites exist in the form of powders, which first need to be prepared with conductive agents and binders to prepare slurries, and then evenly coated on the current collector. Traditional binders are mostly electronic insulators, and the conductive agent particles are randomly dispersed in the electrode, making it impossible to form a continuous electron path in the entire electrode, so that the energy storage capacity of the electrode material cannot be fully utilized, resulting in a low specific capacity.
[0007] How to provide a negative electrode material that can improve the specific capacity, cycle stability and rate performance of transition metal oxide negative electrode batteries is an urgent problem to be solved in this field. Summary of the invention
[0008] In view of the deficiencies of the prior art, the present invention provides a transition metal oxide / conductive polymer gel and a preparation method thereof, a negative electrode active material, a negative electrode plate, and a lithium ion battery. The present invention prepares a transition metal oxide and mixes it with a conductive polymer monomer, phytic acid, etc. to obtain a transition metal oxide / conductive polymer gel, and the preparation method is simple. And due to the viscosity and excellent conductivity of the polymer gel, the prepared transition metal oxide / conductive polymer gel contains a transition metal oxide with a high specific capacity, and also realizes the bonding effect and the conductive function. It is directly used as a negative electrode material and can be directly coated on a copper foil to prepare a negative electrode of a lithium ion battery, avoiding the use of a binder, a conductive agent, a solvent, etc., simplifying the electrode preparation process and reducing the production cost; at the same time, the prepared gel has excellent electrochemical properties, good interface compatibility with the electrolyte, and has a three-dimensional continuous electron transport network, which can promote the full use of the specific capacity of the transition metal oxide as a negative electrode material, improve the specific capacity, cycle stability and rate performance of the battery, and in addition, the material has the potential for large-scale production, which provides the possibility for the performance improvement and application expansion of lithium ion batteries.
[0009] The technical solution of the present invention is as follows:
[0010] The first aspect of the present invention provides a method for preparing a transition metal oxide / conductive polymer gel, the preparation method comprising the following steps:
[0011] Adding transition metal oxide to conductive polymer monomer-phytic acid aqueous solution, after uniform dispersion, adding ammonium persulfate aqueous solution, and ultrasonicating under ice bath to obtain transition metal oxide / conductive polymer gel;
[0012] The molar ratio of the transition metal oxide to the conductive polymer monomer is 0.38-0.63:0.05-1.2;
[0013] And / or, the molar ratio of the conductive polymer monomer to the phytic acid is 0.05-1.2:0.03-0.5.
[0014] Preferably, the molar ratio of the transition metal oxide to the conductive polymer monomer is 0.38-0.63:0.1-1;
[0015] and / or, the molar ratio of the conductive polymer monomer to the phytic acid is 0.1-1:0.03-0.3;
[0016] The transition metal oxide includes at least one of MnO, NiO, FeO, CoO, CuO2, MnO2, Fe2O3, Fe3O4, Co3O4, and CuO;
[0017] and / or, the transition metal oxide comprises at least one of nanoparticles, nanorods, nanosheets, and nanowires;
[0018] Preferably, the transition metal oxide is a transition metal oxide nanorod, more preferably, the transition metal oxide is an α-Fe2O3 nanorod;
[0019] The length of the transition metal oxide nanorods is 50-150 nm.
[0020] Preferably, the conductive polymer monomer includes at least one of aniline, pyrrole and thiophene;
[0021] and / or, in the conductive polymer monomer-phytic acid aqueous solution, the molar concentration of the conductive polymer monomer is 0.1-1 mmol / mL, and the molar concentration of the phytic acid is 0.03-0.3 mmol / mL;
[0022] and / or, the molar concentration of the aqueous ammonium persulfate solution is 0.25-1.25 mmol / mL;
[0023] and / or, the molar ratio of the aniline to the ammonium persulfate is 0.1-1:0.25-0.5;
[0024] And / or, the power of the ultrasound is 400-700 W, and the time is 2-5 min.
[0025] The second aspect of the present invention provides a transition metal oxide / conductive polymer gel prepared by the preparation method described in the first aspect.
[0026] The third aspect of the present invention provides a negative electrode material, comprising the transition metal oxide / conductive polymer gel prepared by the preparation method described in the first aspect, or the transition metal oxide / conductive polymer gel described in the second aspect.
[0027] A fourth aspect of the present invention provides a negative electrode plate, comprising a current collector and a negative electrode material layer coated on at least one surface of the current collector, wherein the negative electrode material layer comprises the negative electrode material described in the third aspect above;
[0028] The peeling force between the negative electrode material and the current collector is ≥0.16N / 20mm.
[0029] Preferably, the preparation method of the negative electrode plate is: coating the above-mentioned negative electrode material on at least one surface of the current collector, standing for reaction, washing, and drying to obtain a negative electrode plate containing a transition metal oxide / conductive polymer gel negative electrode material layer.
[0030] Preferably, in the negative electrode sheet, the surface density of the transition metal oxide / conductive polymer gel negative electrode material layer is 0.5-2.0 mg / cm 2 ;
[0031] And / or, the thickness of the transition metal oxide / conductive polymer gel negative electrode material layer is 50-200 μm.
[0032] Preferably, the temperature of the static reaction is 1-6°C and the time is 6-24h.
[0033] A fifth aspect of the present invention provides a lithium-ion battery, comprising a lithium sheet, a separator, an electrolyte, and the above-mentioned negative electrode sheet.
[0034] The beneficial technical effects of the present invention are:
[0035] The present invention prepares a transition metal oxide / conductive polymer gel negative electrode material by mixing a transition metal oxide with a polymer monomer, phytic acid, etc., and the preparation method is simple. Phytic acid is used as both a dopant and a cross-linking agent to promote the formation of a three-dimensional continuous porous network polymer gel, while giving the gel excellent conductivity and sufficient viscosity. Specifically: on the one hand, phytic acid can form hydrogen bonds with MO (M represents transition metals Fe, Co, Mo, etc.) groups on the surface of the metal oxide, which is beneficial to the uniform dispersion of the transition metal oxide in the system without dissociation; on the other hand, through the protonation of the phosphoric acid groups in the phytic acid and the N atoms on the polymer chain, doping with the neutral polymer is achieved, thereby giving the polymer conductivity. Phytic acid can also act on multiple polymer chains simultaneously through protonation, thereby acting as a cross-linking agent.
[0036] The transition metal oxide / conductive polymer gel prepared by the present invention is composed of a transition metal oxide uniformly coated with a conductive polymer gel layer, and the oxide particles are connected to each other through the three-dimensional porous network of the conductive polymer gel. The structure of the conductive gel is not only conducive to the rapid transmission of electrons and ions, but also can effectively buffer the stress generated by the volume expansion / contraction of the transition metal oxide during the cyclic charge and discharge process, greatly promoting the energy storage capacity of the transition metal oxide and the improvement of the cycle stability; the three-dimensional continuous electron transfer network of the polymer also ensures the efficient electron transmission of the transition metal oxide electrode material during the charge and discharge process. At the same time, the shell of the conductive polymer has good interface compatibility with the electrolyte, that is, because the coating layer is a gel, the electrolyte can be easily wetted, and the electrolyte ions can quickly contact the active sites of the metal oxide through the conductive polymer gel layer, thereby reducing the interface impedance, thereby giving full play to its energy storage capacity, and the prepared battery has a high specific capacity, cycle stability and rate performance.
[0037] In addition, the transition metal oxide / conductive polymer gel electrode material has sufficient conductivity and viscosity, and can be directly coated on copper foil to prepare lithium-ion battery negative electrodes without adding additional conductive agents and binders, which simplifies the electrode preparation process and reduces production costs.
[0038] The preparation method of the present invention, i.e. the prepared transition metal oxide / conductive polymer gel negative electrode material, has the potential for large-scale production and is suitable for large-scale application fields such as electric vehicles and grid energy storage, providing strong support for the performance improvement and application expansion of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a SEM photograph of the α-Fe2O3 nanorods prepared in Example 1 of the present invention.
[0040] Figure 2 This is a characterization diagram of the α-Fe2O3 / PANi gel prepared in Example 1 of the present invention.
[0041] In the figure: a, SEM image of α-Fe2O3 / PANi gel prepared in Example 1; b, TEM image of α-Fe2O3 / PANi gel prepared in Example 1.
[0042] Figure 3 It is the specific capacity of the button-type lithium ion half-cell in Example 1 of the present invention and Comparative Example 1 at different rates.
[0043] Figure 4 It is the long cycle performance at 0.1C of the button-type lithium ion half-cell in Example 1 and Comparative Example 1 of the present invention.
[0044] Figure 5It is an AC impedance test diagram of the button-type lithium-ion half-cell in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0045] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments.
[0046] The first aspect of the present invention provides a method for preparing a transition metal oxide / conductive polymer gel, the preparation method comprising the following steps:
[0047] The transition metal oxide is added into the conductive polymer monomer-phytic acid aqueous solution, and after being evenly dispersed, an ammonium persulfate aqueous solution is added, and ultrasonication is performed under ice bath to obtain a transition metal oxide / conductive polymer gel.
[0048] It can be understood that the present invention prepares the transition metal oxide / conductive polymer gel negative electrode material by mixing the transition metal oxide with the polymer monomer, phytic acid, etc., and the preparation method is simple. Phytic acid is used as both a dopant and a cross-linking agent to promote the formation of a three-dimensional continuous porous network polymer gel, while giving the gel excellent conductivity and sufficient viscosity. Specifically: on the one hand, phytic acid can form hydrogen bonds with the MO (M represents transition metals Fe, Co, Mo, etc.) groups on the surface of the metal oxide, which is beneficial to the uniform dispersion of the transition metal oxide in the system without dissociation; on the other hand, through the protonation of the phosphoric acid groups in the phytic acid and the N atoms on the polymer chain, the doping of the neutral polymer is achieved, thereby giving the polymer conductivity. Phytic acid can also act on multiple polymer chains simultaneously through protonation, and act as a cross-linking agent.
[0049] The transition metal oxide / conductive polymer gel in the present invention is composed of a transition metal oxide uniformly coated with a conductive polymer gel layer, and the oxide particles are connected to each other through the three-dimensional porous network of the conductive polymer gel. The structure of the conductive gel is not only conducive to the rapid transmission of electrons and ions, but also can effectively buffer the stress generated by the volume expansion / contraction of the transition metal oxide during the cyclic charge and discharge process, greatly promoting the energy storage capacity of the transition metal oxide and the improvement of the cycle stability; the three-dimensional continuous electron transfer network of the polymer also ensures the efficient electron transfer of the transition metal oxide electrode material during the charge and discharge process. At the same time, the shell of the conductive polymer has good interface compatibility with the electrolyte, that is, because the coating layer is a gel, the electrolyte can be easily wetted, and the electrolyte ions can quickly pass through the conductive polymer gel layer to contact the active sites of the metal oxide, thereby reducing the interface impedance, thereby giving full play to its energy storage capacity, and the prepared battery has a high specific capacity, cycle stability and rate performance.
[0050] It is understandable that the transition metal oxide / conductive polymer gel electrode material of the present invention has sufficient conductivity and viscosity, and can be directly coated on copper foil to prepare lithium-ion battery negative electrode without adding additional conductive agents and binders, which simplifies the electrode preparation process and reduces production costs.
[0051] In some embodiments, the molar ratio of the transition metal oxide to the conductive polymer monomer is 0.38-0.63:0.05-1.2, including but not limited to 0.38:0.05, 0.38:1.2, 0.63:0.05, 0.63:1.2, 0.5:0.3; the molar ratio of the conductive polymer monomer to the phytic acid is 0.05-1.2:0.03-0.5, including but not limited to 0.05:1.2, 0.05:0.5, 1.2:0.03, 1.2:0.5, 1.0:0.1, 1:0.3. Preferably, the molar ratio of the transition metal oxide to the conductive polymer monomer is 0.38-0.63:0.1-1; the molar ratio of the conductive polymer monomer to the phytic acid is 0.1-1:0.03-0.3.
[0052] It is understandable that the present invention prepares a gel having a certain viscosity, conductivity and three-dimensional network structure by controlling the amount of transition metal oxide, polymer monomer and phytic acid. When the ratio of the three substances is changed, especially when the relative ratio of the metal oxide to the polymer monomer is too large, the polymer conductive gel will be unevenly coated on the surface of the metal oxide, reducing the conductivity of the active material electrode, thereby affecting the performance of the electrical properties. When the relative ratio is too small, although the polymer gel can achieve complete coating of the metal oxide particles and form a continuous electron transfer network, the relative content of the metal oxide in the transition metal oxide / conductive polymer gel will be reduced, which is not conducive to the high specific capacity of the material when used as a negative electrode active material of a lithium battery.
[0053] It can be understood that the present invention limits the ratio between the transition metal oxide, the polymer monomer and the cross-linking agent. When the polymer monomer undergoes an in-situ polymerization reaction on the surface of the transition metal oxide, the transition metal oxide can be covered with the conductive gel to the greatest extent possible. The three-dimensional porous network connection structure formed by the conductive polymer gel and the transition metal oxide can be used to achieve rapid transmission of electrons and lithium ions, effectively buffer the stress generated by the volume expansion / contraction of the transition metal oxide during the cyclic charge and discharge process, and solve the problem that the transition metal oxide is not completely coated and cannot fully contact with the electrolyte, which will reduce the energy storage capacity. This greatly promotes the energy storage capacity of the transition metal oxide and improves the cycle stability and specific capacity.
[0054] In some embodiments, the transition metal oxide includes at least one of MnO, NiO, FeO, CoO, CuO2, MnO2, Fe2O3, Fe3O4, Co3O4, and CuO; as an example, the present invention verifies the transition metal oxide using α-Fe2O3 as a representative.
[0055] In some embodiments, the transition metal oxide includes at least one of nanoparticles, nanorods, nanosheets, and nanowires. In the present invention, the effects of nanorods, nanosheets, and nanowires are significantly better than nanoparticles, so the transition metal oxide morphology of the present invention is preferably nanorods.
[0056] In some embodiments, the transition metal oxide is a transition metal oxide nanorod, more preferably, the transition metal oxide is an α-Fe2O3 nanorod.
[0057] In some embodiments, the length of the transition metal oxide nanorods is 50-150 nm, including but not limited to 50 nm, 100 nm, and 150 nm.
[0058] It can be understood that the present invention limits the size of transition metal oxides so that the obtained gel material contains transition metal oxides of a specific size. When the size of the metal oxide is too small, the particles tend to agglomerate, and many of them cannot contact the electrolyte, resulting in a significant reduction in energy storage capacity. When the size is too large, the specific surface area of the metal oxide is reduced, and when the conductive polymer is in situ polymerized on its surface, the effective contact area with the electrolyte is also reduced, resulting in its Li storage capacity being too small. + ability has been greatly reduced.
[0059] In some embodiments, the conductive polymer monomer includes at least one of aniline, pyrrole, and thiophene.
[0060] And / or, in the conductive polymer monomer-phytic acid aqueous solution, the molar concentration of the conductive polymer monomer is 0.1-1 mmol / mL, including but not limited to 0.1 mmol / mL, 0.2 mmol / mL, 0.4 mmol / mL, 0.6 mmol / mL, 0.8 mmol / mL, 1 mmol / mL, and the molar concentration of phytic acid is 0.03-0.3 mmol / mL, including but not limited to 0.03 mmol / mL, 0.1 mmol / mL, 0.2 mmol / mL, 0.3 mmol / mL.
[0061] In some embodiments, the molar concentration of the aqueous ammonium persulfate solution is 0.25-1.25 mmol / mL, including but not limited to 0.25 mmol / mL, 0.5 mmol / mL, 1.0 mmol / mL, and 1.25 mmol / mL.
[0062] In some embodiments, the molar ratio of the aniline to the ammonium persulfate is 0.1-1:0.25-0.5, including but not limited to 0.1:0.25, 1:0.25, 0.1:0.5, 1:0.5, 0.5:0.3.
[0063] In some embodiments, the power of the ultrasound is 400-700 W, including but not limited to 400 W, 500 W, 600 W, and 700 W, and the time is 2-5 min, including but not limited to 2 min, 3 min, 4 min, and 5 min.
[0064] The second aspect of the present invention provides a transition metal oxide / conductive polymer gel prepared by the preparation method described in the first aspect.
[0065] The third aspect of the present invention provides a negative electrode material, comprising the transition metal oxide / conductive polymer gel prepared by the preparation method described in the first aspect, or the transition metal oxide / conductive polymer gel described in the second aspect.
[0066] It is understandable that the present invention directly uses transition metal oxide / conductive polymer gel as a negative electrode material to form an active material layer, avoiding the use of a binder. At the same time, by limiting the thickness and surface density of the active material layer, it is ensured that the maximum activity of the active material is exerted under conditions of practical application significance. If the thickness or surface density is too large, the transmission path of lithium ions will be increased, the specific capacity of the material will be reduced, and the performance of the rate discharge and long cycle electrical performance will be degraded. If the thickness or surface density is too small, it will not meet the application direction of high energy density and the application of high coating electrodes.
[0067] The fourth aspect of the present invention provides a negative electrode plate, including a current collector and a negative electrode material layer arranged on at least one surface of the current collector, wherein the negative electrode material layer includes the negative electrode material described in the third aspect above; the peeling force between the negative electrode material and the current collector is ≥0.16N / 20mm.
[0068] In some embodiments, the preparation method of the negative electrode plate is: coating the above-mentioned negative electrode material on at least one surface of the current collector, standing for reaction, rinsing, and drying to obtain a negative electrode plate containing a transition metal oxide / conductive polymer gel negative electrode material layer.
[0069] In some embodiments, in the negative electrode sheet, the surface density of the transition metal oxide / conductive polymer gel negative electrode material layer is 0.5-2.0 mg / cm 2 , including but not limited to 0.5 mg / cm 2 , 1.0mg / cm 2 , 1.5mg / cm 2, 2.0mg / cm 2 .
[0070] In some embodiments, the thickness of the transition metal oxide / conductive polymer gel negative electrode material layer is 50-200 μm, including but not limited to 50 μm, 100 μm, 150 μm, and 200 μm.
[0071] In some embodiments, the temperature of the static reaction is 1-6°C, including but not limited to 1°C, 2°C, 3°C, 4°C, 5°C, 6°C, and the time is 6-24h, including but not limited to 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h.
[0072] A fifth aspect of the present invention provides a lithium-ion battery, comprising a lithium sheet, a separator, an electrolyte, and the above-mentioned negative electrode sheet.
[0073] In some embodiments, the transition metal oxide is preferably Fe2O3, and more preferably, the iron oxide is α-Fe2O3, and the preparation method thereof is:
[0074] (1) Dissolve ferric chloride hexahydrate in deionized water and then add sodium nitrate to make a clear solution.
[0075] (2) Hydrochloric acid was added dropwise to adjust the pH of the solution, and the prepared clear solution was transferred to a polytetrafluoroethylene-lined reactor. After a period of reaction, the solution was naturally cooled to room temperature, and centrifuged and washed to obtain yellow β-FeOOH powder.
[0076] (3) The dried yellow powder is placed in a muffle furnace and calcined. The yellow powder turns red, and α-Fe2O3 nanorods are obtained.
[0077] In some embodiments, the amount of ferric chloride hexahydrate added is 0.2-1.2g, including but not limited to 0.2g, 0.4g, 0.6g, 0.8g, 1.0g, 1.2g, the volume of deionized water is 10-20mL, including but not limited to 10mL, 12mL, 14mL, 16mL, 18mL, 20mL, the amount of sodium nitrate added is 0.8-2g, including but not limited to 0.8g, 1.0g, 1.5g, 2.0g. The pH is 1-2, including but not limited to 1, 2; the reaction temperature is 80-110℃, including but not limited to 80℃, 90℃, 100℃, 110℃, the time is 3-5h, including but not limited to 3h, 4h, 5h, the calcination temperature is 400-600℃, including but not limited to 400℃, 500℃, 600℃, and the calcination time is 2-4h, including but not limited to 2h, 3h, 4h.
[0078] In the present invention, the particle size or length of the transition metal oxide nanorods is tested by using a laser particle size analyzer to measure the particle size distribution of the entire nanorods, and a scanning electron microscope to measure the specific length of certain specific particles.
[0079] In some embodiments of the present invention, the negative electrode current collector comprises at least one of copper foil, carbon-coated copper foil, and composite copper foil. The present application has no particular limitation on the thickness of the negative electrode current collector, and any thickness that can achieve the purpose of the present invention is within the protection scope of the present invention. For example, the thickness of the negative electrode current collector is 10-30 μm.
[0080] In some embodiments of the present invention, the electrolyte is at least one of a liquid organic electrolyte and a gel electrolyte. Exemplarily, the electrolyte is a liquid organic electrolyte. The liquid organic electrolyte includes an electrolyte, a solvent and an additive. Among them, the electrolyte includes one or more of lithium difluorophosphate LiPO2F2, lithium difluorooxalate phosphate LiDFOP, lithium difluorooxalate borate LiDFOB, lithium bis(fluorosulfonyl)imide LiFSI, lithium bis(trifluoromethanesulfonyl)imide LiTFSi, lithium tetrafluoroborate LiBF4, and lithium hexafluorophosphate LiPF6. The solvent includes one or more of ethylene carbonate EC, propylene carbonate PC, diethyl carbonate DEC, dimethyl carbonate DMC, ethyl methyl carbonate EMC, methyl acetate MA, ethyl acetate EA, and ethyl propionate EP. The additive comprises one or more of vinylene carbonate VC, vinyl vinyl carbonate VEC, vinyl sulfate DTD, vinyl sulfite ES, methylene methanedisulfonate MMDS, 1,3-propane sultone PS, propene sultone PES, propylene sulfate TMS, trimethylsilyl phosphate TMSP, trimethylsilyl borate TMSB, and fluoroethylene carbonate FEC.
[0081] In some embodiments, the electrolyte is: 1M LiPF6, EC / DMC / DEC (the volume ratio of EC, DMC, DEC is 1:2:1). It is understood that in the present invention, the electrolyte of the corresponding type and composition can be selected according to the needs, and the present invention is not limited to this.
[0082] It is understandable that the present invention does not limit the diaphragm, and any solution that can achieve the purpose of the present invention is within the protection scope of the present invention. Exemplarily, the diaphragm is a polypropylene diaphragm.
[0083] The present invention will be further described below by way of examples and the like.
[0084] Example 1
[0085] The preparation method of α-ferric oxide / polyaniline gel comprises the following steps:
[0086] S1: Preparation of α-Fe2O3
[0087] (1) Dissolve 0.811 g of ferric chloride hexahydrate in 20 mL of deionized water, and then add 1.698 g of sodium nitrate to prepare a clear solution.
[0088] (2) Hydrochloric acid was added dropwise to adjust the pH of the solution to 1.5, and the prepared clear solution was transferred to a 25 mL polytetrafluoroethylene-lined reactor. The mixture was placed in a 95°C oven for 4 h, cooled naturally to room temperature, and centrifuged to wash and collect the yellow β-FeOOH powder.
[0089] (3) Finally, the dried yellow powder was calcined in a muffle furnace at 550°C for 2 h. The yellow powder turned red, and α-Fe2O3 nanorods with an average length of 100 nm were obtained.
[0090] S2: Under the sequential action of magnetic stirring and ultrasound, 90 mg (0.56 mmol) of α-Fe2O3 nanorods were uniformly dispersed in 1 mL of aqueous solution containing 0.5 mmol of aniline and 0.15 mmol of phytic acid; then, 0.5 mL of aqueous solution containing 0.3 mmol of ammonium persulfate was added to the above system, and ultrasound was applied in an ice bath for 3 min, and ultrasound was applied in an ice bath to obtain a sticky α-Fe2O3 / PANi gel.
[0091] The negative electrode sheet containing the above-mentioned α-ferric oxide / polyaniline gel is prepared by:
[0092] The viscous α-Fe2O3 / PANi gel was coated on the copper foil using a film applicator.
[0093] The copper foil coated with α-Fe2O3 / PANi gel was placed in a refrigerator at 4°C for 8 hours. After the polymerization reaction was complete, the byproducts such as aniline oligomers and unreacted phytic acid were removed by washing with ethanol. The α-Fe2O3 / PANi gel electrode was obtained by drying at room temperature. The surface density of the negative electrode material layer was 1 mg / cm 2 .
[0094] A button-type lithium-ion half-cell comprises a negative electrode sheet containing the above-mentioned α-ferric oxide / polyaniline gel, and the preparation method thereof is as follows:
[0095] In a glove box, the prepared α-Fe2O3 / PANi gel anode sheet, Celgard2400 polypropylene separator, and lithium metal sheet were stacked to ensure isolation of the two electrodes. 1M LiPF6EC / DMC / DEC (1:2:1 v / v) electrolyte (300 μL) was injected and packaged into a CR2032 button cell under vacuum conditions.
[0096] Example 2
[0097] An alpha-ferric oxide / polyaniline gel, the preparation method of which is substantially the same as that of Example 1, except that the molar ratio of transition metal oxide to aniline is changed to 0.56:1.0, and the molar ratio of aniline to phytic acid is changed to 2:0.6.
[0098] A negative electrode plate containing the above-mentioned α-ferric oxide / polyaniline gel, the preparation method of which is the same as that of Example 1.
[0099] A button-type lithium-ion half-cell comprises a negative electrode plate containing the above-mentioned α-ferric oxide / polyaniline gel, and its preparation method is the same as that of Example 1.
[0100] Example 3
[0101] An alpha-ferric oxide / polyaniline gel, the preparation method of which is substantially the same as that of Example 1, except that the molar ratio of transition metal oxide to aniline is changed to 0.56:0.1, and the molar ratio of aniline to phytic acid is changed to 3:1.
[0102] A negative electrode plate containing the above-mentioned α-ferric oxide / polyaniline gel, the preparation method of which is the same as that of Example 1.
[0103] A button-type lithium-ion half-cell comprises a negative electrode plate containing the above-mentioned α-ferric oxide / polyaniline gel, and its preparation method is the same as that of Example 1.
[0104] Example 4
[0105] An α-ferric oxide / polyaniline gel, the preparation method of which is basically the same as that of Example 1, except that the molar ratio of transition metal oxide, aniline, phytic acid and ammonium persulfate is changed. In this embodiment, the molar ratio of transition metal oxide, aniline, phytic acid and ammonium persulfate is 0.56:0.05:0.15:0.3. Fe2O3 / PANi obtained in the embodiment.
[0106] A negative electrode plate containing the above-mentioned α-ferric oxide / polyaniline gel, the preparation method of which is the same as that of Example 1.
[0107] A button-type lithium-ion half-cell comprises a negative electrode plate containing the above-mentioned α-ferric oxide / polyaniline gel, and its preparation method is the same as that of Example 1.
[0108] Example 5
[0109] An alpha-ferric oxide / polyaniline gel, the preparation method of which is basically the same as that of Example 1, except that the molar ratio of transition metal oxide, aniline and phytic acid is changed. In this example, the molar ratio of transition metal oxide, aniline and phytic acid is 0.56:1.2:0.15:0.3.
[0110] A negative electrode plate containing the above-mentioned α-ferric oxide / polyaniline gel, the preparation method of which is the same as that of Example 1.
[0111] A button-type lithium-ion half-cell comprises a negative electrode plate containing the above-mentioned α-ferric oxide / polyaniline gel, and its preparation method is the same as that of Example 1.
[0112] Example 6
[0113] An α-ferric oxide / polyaniline gel, the preparation method of which is the same as that of Example 1.
[0114] A negative electrode sheet containing the above-mentioned α-ferric oxide / polyaniline gel, the preparation method of which is basically the same as that of Example 1, except that the surface density of the negative electrode material layer formed by gel coating is reduced. In this embodiment, the surface density of the transition metal oxide / polyaniline gel negative electrode material layer is 0.5 mg / cm 2 The preparation method of the negative electrode sheet of this embodiment is as follows:
[0115] The viscous α-Fe2O3 / PANi gel was coated on the copper foil with a thickness of 50 μm using a film applicator.
[0116] The copper foil coated with α-Fe2O3 / PANi gel was placed in a refrigerator at 4°C for 8 hours. After the polymerization reaction was complete, the byproducts such as aniline oligomers and unreacted phytic acid were removed by washing with ethanol. The α-Fe2O3 / PANi gel electrode was obtained by drying at room temperature, with a surface density of 0.50 mg / cm 2 .
[0117] A button-type lithium-ion half-cell comprises a negative electrode plate containing the above-mentioned α-ferric oxide / polyaniline gel, and its preparation method is the same as that of Example 1.
[0118] Example 7
[0119] An α-ferric oxide / polypyrrole gel, the preparation method of which is as follows:
[0120] S1: Prepare α-ferric oxide (α-Fe2O3), the preparation method of which is the same as that in Example 1.
[0121] S2: Under the sequential action of magnetic stirring and ultrasound, 90 mg (0.56 mmol) of α-Fe2O3 nanorods were uniformly dispersed in 1 mL of aqueous solution containing 0.5 mmol of pyrrole and 0.15 mmol of phytic acid; then, 0.5 mL of aqueous solution containing 0.3 mmol of ammonium persulfate was added to the above system, and ultrasound was applied for 3 min in an ice bath to obtain a sticky α-Fe2O3 / polypyrrole (α-Fe2O3 / Ppy) gel.
[0122] The negative electrode sheet containing the above-mentioned α-ferric oxide / polypyrrole gel is prepared by:
[0123] The viscous α-Fe2O3 / Ppy gel was coated on the copper foil using a film applicator.
[0124] The copper foil coated with α-Fe2O3 / Ppy gel was placed in a refrigerator at 4°C for 24 hours. After the polymerization reaction was complete, the byproducts such as aniline oligomers and unreacted phytic acid were removed by washing with ethanol. The α-Fe2O3 / ppy gel electrode was obtained by drying at room temperature. The surface density of the negative electrode material layer was 1 mg / cm 2 .
[0125] A button-type lithium-ion half-cell comprises a negative electrode sheet containing the above-mentioned α-ferric oxide / polypyrrole gel, and its preparation method is the same as that of Example 1.
[0126] Comparative Example 1
[0127] A negative electrode slurry is prepared by weighing a certain amount of α-ferric oxide (α-Fe2O3), a conductive agent acetylene black, and a binder PVDF prepared in Example 1 according to a mass activity ratio of 8:1:1, adding an appropriate amount of N-methylpyrrolidone (NMP) to dissolve, stirring and dispersing, and forming a viscous slurry, which is the negative electrode slurry.
[0128] The slurry was coated on the copper foil in the coating method of Example 1. The sample was then placed in a vacuum drying oven at 90° C. for overnight (12 h) drying to obtain a negative electrode sheet.
[0129] The assembly method of the button battery is basically the same as that of Example 1, except that the negative electrode sheet of Example 1 is replaced with the negative electrode sheet prepared in Comparative Example 1.
[0130] Comparative Example 2
[0131] A negative electrode slurry, the preparation method of which is:
[0132] (1) Prepare α-Fe2O3 according to the method of Example 1.
[0133] (2) To 1 mL of aqueous solution containing 0.5 mmol of aniline and 0.15 mmol of phytic acid, 0.5 mL of aqueous solution containing 0.3 mmol of ammonium persulfate was added, and the mixture was sonicated for 3 min in an ice bath, and then sonicated in an ice bath to obtain a sticky PANi gel.
[0134] (3) Ultrasonication and stirring are performed to uniformly mix α-Fe2O3 and PANi gel to obtain a negative electrode slurry.
[0135] The negative electrode slurry was coated on the copper foil in the coating method of Example 1. The sample was then placed in a vacuum drying oven at 90° C. for overnight (12 h) drying to obtain a negative electrode sheet.
[0136] The assembly method of the button cell is substantially the same as that of Example 1, except that the negative electrode sheet of Example 1 is replaced with the negative electrode sheet prepared in Comparative Example 2.
[0137] Comparative Example 3
[0138] An α-ferric oxide / polyaniline gel, the preparation method of which is the same as that of Example 1.
[0139] A negative electrode sheet containing the above-mentioned α-ferric oxide / polyaniline gel, the preparation method of which is basically the same as that of Example 1, except that the surface density of the negative electrode material layer formed by gel coating is increased. In this comparative example, the surface density of the transition metal oxide / polyaniline gel negative electrode material layer is 2.5 mg / cm 2 The preparation method of the negative electrode sheet of this embodiment is as follows:
[0140] The viscous α-Fe2O3 / PANi gel was coated on the copper foil with a thickness of 250 μm using a film applicator.
[0141] The carbon coated with α-Fe2O3 / PANi gel was placed in a refrigerator at 4°C for 8 hours. After the polymerization reaction was complete, the byproducts such as aniline oligomers and unreacted phytic acid were removed by washing with ethanol. The α-Fe2O3 / PANi gel electrode was obtained by drying at room temperature, with a surface density of 2.5 mg / cm 2 .
[0142] A button-type lithium-ion half-cell comprises a negative electrode plate containing the above-mentioned α-ferric oxide / polyaniline gel, and its preparation method is the same as that of Example 1.
[0143] Test example:
[0144] 1. Performance test of α-ferric oxide / polyaniline gel material
[0145] The SEM photo of the α-iron oxide nanorods prepared in Example 1 of the present invention is as follows: Figure 1 As shown in the figure, it can be seen that the diameter of the prepared α-Fe2O3 nanorods is about 100nm.
[0146] The structure of the α-ferric oxide / polyaniline gel material prepared in Example 1 of the present invention is as follows: Figure 2 As shown in the figure, it can be seen that the α-Fe2O3 / PANi gel is composed of α-Fe2O3 nanorods uniformly coated with a polyaniline gel layer, and the nanorods are connected to each other through the three-dimensional network of polyaniline gel on their surface.
[0147] 2. Peel force test:
[0148] The negative electrode sheets prepared in the examples and comparative examples were peeled off at 180°, and the peeling strength was used to measure the bonding performance between the negative electrode coating material and the current collector (copper foil).
[0149] The test was conducted using an intelligent electronic tensile testing machine. The adhesion strength of the coating on the electrode surface was evaluated by testing the force required for the adhesive tape to peel the coating from the copper foil surface. During the test, the test fixture was clamped in the lower fixture, which was fixed, the free end of the copper foil was fixed in the upper fixture, and the tape used to adhere the coating was fixed in the lower fixture. The fixture can move upward at a set speed, thereby driving the adhesive tape to peel the coating from the foil surface. The force sensor configured in the upper fixture records the force generated during the peeling process in real time, and the average value of the force is recorded as the peeling force value of the electrode coating. The results are shown in Table 1.
[0150] 3. Battery electrochemical performance test
[0151] The electrochemical performance of the batteries corresponding to the embodiments and comparative examples was tested, and the results are shown in Table 1. The specific test method is as follows:
[0152] The electrochemical test was carried out at room temperature (25±1)℃, and the LAND CT2001A battery charge and discharge instrument was used to test the specific capacity, rate performance and cycle performance by constant current charge and discharge. The results are shown in Table 1 and the attached figure. The cycle performance is the reversible capacity after 100 times. The current used in the test of charge and discharge capacity is 0.1C. Set the test parameters: the charge and discharge voltage range is 0.01V to 3V.
[0153] The rate performance mainly tests the charge and discharge capacity of lithium-ion batteries at different currents under room temperature. The current is 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 10C and then returns to 0.1C. It mainly tests the charge and discharge results of the battery under high current and then returns to 0.1C low current test to explore the stability of the material.
[0154] The instrument used for the alternating current impedance test (EIS) was the CHI760E electrochemical workstation produced by Shanghai Chenhua Instrument Co., Ltd. The test frequency range was 0.01 Hz-1000 kHz, and the amplitude was 5 mV.
[0155] Table 1: Peeling force of negative electrode sheets prepared in the examples and comparative examples and performance of negative electrode button cells obtained in the examples and comparative examples
[0156]
[0157]
[0158] It can be seen from the peeling performance in Table 1 that the peeling force of the gel negative electrode sheet is higher than that of the conventional negative electrode sheet, which means that the gel negative electrode has stronger adhesion to the current collector, which is more conducive to reducing the electrochemical impedance and achieving better electrochemical performance. From the electrochemical performance test in Table 1, it can be seen that the gel negative electrode exhibits higher charge and discharge specific capacity, first efficiency and more stable long cycle life performance than the control group.
[0159] In addition, it can be seen from the electrochemical performance test results in Table 1 that the gel negative electrodes of Examples 1-4, 6-7 show higher charge and discharge specific capacity, first effect and more stable long cycle life performance than Comparative Example 1, which is due to the good electrode structure of the transition metal oxide / polymer conductive gel. The specific capacity of Example 5 is lower than that of the comparative example because the proportion of active material metal oxide is small, and the effective capacity is low, but the cycle life still shows obvious advantages over Comparative Example 1 due to the uniform coating of the conductive gel. Although Example 6 has better electrical properties, this is the result obtained at the expense of surface density. The overall effect is better than that of the comparative example, but the disadvantage is that it is not conducive to the practical application of high energy density. Comparative Example 2 prepares α-Fe2O3 and PANi conductive gel separately, and then simply physically mixes the two. Its electrical properties are not significantly improved compared with Comparative Example 1. This is mainly because the polymer cannot be evenly coated on the surface of α-Fe2O3 during physical mixing, so it cannot assist α-Fe2O3 to significantly improve the energy storage capacity. In Comparative Example 3, since the surface density of the electrode is too high, the transmission distance of lithium ions in the electrode becomes longer and the kinetics becomes worse, thus affecting the electrical performance.
[0160] Figure 3 The specific capacity of the button-type lithium-ion half-cell in Example 1 and Comparative Example 1 of the present invention at different rates. Figure 3 It can be seen that the capacity retention rate of the battery prepared in Example 1 of the present invention at 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 10C and then back to 0.1C is significantly better than that of Comparative Example 1 at the same rate, indicating that the electrode prepared in Example 1 of the present invention has better kinetic performance, which is determined by the high electron and lithium ion transport characteristics of the electrode material in Example 1.
[0161] Figure 4 The long cycle performance of the button-type lithium ion half-cell at 0.1C in Example 1 and Comparative Example 1 of the present invention. Figure 4It can be seen that the cycle performance of the battery prepared in Example 1 of the present invention is significantly higher than that of Comparative Example 1 in terms of cycle life within 100 weeks, which means that the structural stability of the electrode prepared in Example 1 is significantly better than that of Comparative Example 1. This is mainly because the interpenetrating 3D conductive polymer network of the electrode prepared in Example 1 reserves space for buffering the volume expansion of α-Fe2O3 during a long cycle, thereby better maintaining the stability of the electrode structure, while the α-Fe2O3 nanorods of Comparative Example 1 cause structural collapse and pulverization during a long cycle.
[0162] Figure 5 The EIS diagram of the button-type lithium-ion half-cell in Example 1 and Comparative Example 1 of the present invention is shown in FIG. Figure 5 It can be seen that in the semicircular shape in the high-frequency region, corresponding to the interface transfer impedance part, it can be seen that the battery prepared in Example 1 of the present invention is significantly smaller than that in Comparative Example 1, indicating that the α-Fe2O3 / PANi gel prepared in Example 1 has higher electronic conductivity than the pure α-Fe2O3 nanorod material prepared in Comparative Example 1, and can effectively reduce the interface impedance. The oblique line part in the low-frequency region corresponds to the diffusion impedance, and it can also be seen that the battery prepared in Example 1 has a significantly higher slope than that in Comparative Example 1, which means that the α-Fe2O3 / PANi gel prepared in Example 1 is more conducive to the transmission of lithium ions than the pure α-Fe2O3 nanorod material prepared in Comparative Example, which is due to the 3D network structure of the polymer shell and the good interface compatibility, which promotes the transmission of lithium ions and reduces the diffusion impedance.
[0163] The transition metal oxide / conductive polymer composite material constructed by the present invention has good interface compatibility between the conductive polymer shell and the electrolyte, and the prepared electrode has a three-dimensional continuous electron transfer network, which can promote the full utilization of the specific capacity of the transition metal oxide as a negative electrode material.
[0164] The above is only a preferred embodiment of the present invention, and the present invention is not limited to the above embodiments. It is understood that other improvements and changes directly derived or associated by those skilled in the art without departing from the spirit and concept of the present invention should be considered to be included in the protection scope of the present invention.
Claims
1. A method for preparing a transition metal oxide / conductive polymer gel, characterized in that: The preparation method comprises the following steps: Adding transition metal oxide to conductive polymer monomer-phytic acid aqueous solution, after uniform dispersion, adding ammonium persulfate aqueous solution, and ultrasonicating under ice bath to obtain transition metal oxide / conductive polymer gel; The molar ratio of the transition metal oxide to the conductive polymer monomer is 0.38-0.63:0.05-1.2; And / or, the molar ratio of the conductive polymer monomer to the phytic acid is 0.05-1.2:0.03-0.
5.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the transition metal oxide to the conductive polymer monomer is 0.38-0.63:0.1-1; and / or, the molar ratio of the conductive polymer monomer to the phytic acid is 0.1-1:0.03-0.3; And / or, the transition metal oxide includes at least one of MnO, NiO, FeO, CoO, CuO2, MnO2, Fe2O3, Fe3O4, Co3O4, CuO; and / or, the transition metal oxide comprises at least one of nanoparticles, nanorods, nanosheets, and nanowires; Preferably, the transition metal oxide is a transition metal oxide nanorod, more preferably, the transition metal oxide is an α-Fe2O3 nanorod; The length of the transition metal oxide nanorods is 50-150 nm.
3. The preparation method according to claim 1, characterized in that: The conductive polymer monomer includes at least one of aniline, pyrrole and thiophene; and / or, in the conductive polymer monomer-phytic acid aqueous solution, the molar concentration of the conductive polymer monomer is 0.1-1 mmol / mL, and the molar concentration of the phytic acid is 0.03-0.3 mmol / mL; and / or, the molar concentration of the aqueous ammonium persulfate solution is 0.25-1.25 mmol / mL; and / or, the molar ratio of the aniline to the ammonium persulfate is 0.05-1.2:0.25-0.5, preferably, the molar ratio of the aniline to the ammonium persulfate is 0.1-1:0.25-0.5; And / or, the power of the ultrasound is 400-700 W, and the time is 2-5 min.
4. A transition metal oxide / conductive polymer gel prepared by the preparation method according to any one of claims 1 to 3.
5. A negative electrode material, characterized in that: The invention comprises a transition metal oxide / conductive polymer gel prepared by the preparation method according to any one of claims 1 to 3, or a transition metal oxide / conductive polymer gel according to claim 4.
6. A negative electrode plate, characterized in that: A current collector and a negative electrode material layer coated on at least one surface of the current collector, wherein the negative electrode material layer comprises the negative electrode material according to claim 5; The peeling force between the negative electrode material and the current collector is ≥0.16N / 20mm.
7. The negative electrode sheet according to claim 6, characterized in that: The preparation method of the negative electrode plate is: coating the negative electrode material according to claim 5 on at least one surface of the current collector, standing for reaction, washing, and drying to obtain a negative electrode plate containing a transition metal oxide / conductive polymer gel negative electrode material layer.
8. The negative electrode sheet according to claim 7, characterized in that: In the negative electrode plate, the surface density of the transition metal oxide / conductive polymer gel negative electrode material layer is 0.5-2.0 mg / cm 2 ; And / or the thickness of the transition metal oxide / conductive polymer gel negative electrode material layer is 50-200 μm.
9. The negative electrode sheet according to claim 7, characterized in that: The temperature of the static reaction is 1-6°C and the time is 6-24h.
10. A lithium ion battery, characterized in that: It comprises a lithium sheet, a separator, an electrolyte, and the negative electrode sheet as described in any one of claims 6 to 9.